Nanoscience and nanotechnology in latin America - Nemirovsky, Adolfo; Audebert, Fernando; Oliveira Jr., Osvaldo N.; Constantino, Carlos J.L. [UNESP]; Barrientos, Lorena; González, Guillermo; de la Rosa, Elder (IGI Global, 2010)
Latin America (LA) can count some strong research centers with a tradition of research excellence in certain disciplines such as medicine and biology, nuclear technology, metallurgy and materials, among others. Latin American countries have generated networks of researchers across disciplines, centers, etc. within a country, and linking two or more countries in the region (e.g., Argentina-Brazil Bi-National Center for Nanoscience & Nanotechnology, CABN). Additionally, collaborations have extended beyond LA, mainly to the EU and the USA. In general, these programs have been quite successful in the generation of interdisciplinary nanoscience and nanotechnology (N & N) research. The relation between academia and industry has been improving in the last few years, but it is still weak. In particular, funding incentives for N&N efforts have encouraged joint efforts and contributed to new dimensions in collaborations. This chapter reviews the state of nanoscience and nanotechnology in Chile, Brazil, Argentina and Mexico. © 2010, IGI Global.